Turkish migration in Europe and desire to migrate to and from Turkey - Sirkeci, Ibrahim; Esipova, Neli (Border Crossing, 2013)
Turkey’s accession to the European Union has turned out to be a very long saga. One of the concerns in Europe is that Turkey’s membership would open the way for millions of immigrants from Turkey arriving in Western European member states, as was believed to be the case with Eastern European enlargement in the 2000s. This paper focuses on migration flows and causes of human mobility while drawing upon the Gallup World Poll on migration in Europe with particular reference to the data on desire to migrate permanently from Turkey and to Turkey. The Gallup World Poll is an on-going project surveying residents in more than 150 countries on a variety of topics including international mobility. The full data set includes over 400,000 face-to-face interviews conducted in 2009, 2010 and 2011. Despite exceptions with different sample sizes, in each of the 160 countries 3,000 cases were collected as part of a larger survey. Turkish respondents have lower desire to emigrate compared to the rest of the world while Iranians and Germans are top groups who desire to migrate to Turkey. The data shows that Turkey has been a growing economy and attracting immigration while also producing emigration. Turkey’s overall socio-economic and political record suggests that the desire to migrate from Turkey will continue despite recent economic advances. Nevertheless, the Gallup data shows that the level of desire to migrate in Turkey is remarkably lower than many neighbouring countries and Europe.